A survey on BIM information management: the approach of producers and consumers of model information in Brazil. Issue 9 (1st November 2022) - Oliveira, F M; Santos, E T
Abstract: BIM Information Management, namely how information is introduced in and consumed from building information models, have an impact on the efficacy and efficiency of BIM workflows. Implicit reliance on all the information contained in a model may result in non-value-adding work from model authors. The recommended alternative is creation and use of information according to the Project BIM Execution Plan specifications. Regardless the adopted approach, model asseveration is demanded from authors (i.e., the verification that all required information is reliable and is available on a released model). International standards, such as ISO 19650, require clear and rigorous specification of information need, but anecdotal evidence indicates that the current practices in local markets are far from those recommended by these standards. An extensive online survey was conducted to assess current practices of professionals from the Brazilian market. Results showed that about half of the respondents adopt document-based (MEA/MET) recommended practices when dealing with model information, while the other half kept a behaviour more akin to the older CAD workflows. The implicit reliance (without checking MEA/MET documents) on model information varies according to professional role, being lower for design professionals and coordinators and higher for construction managers. As standards evolve and introduce new concepts for deeper and more granular information management, such as the Level of Information Need, it is necessary that professionals adapt their practices for increased efficiency on their BIM workflows.